Local Wisdom-Based Character Values on Kawali’s Inscription In History Learning - Pajriah, Sri; Suryana, Aan (Paramita: Historical Studies Journal, 2021)
This study aims to describe the character values of Kawali’s Inscription and the implementation of local wisdom-based character values on Kawali’s Inscription in history learning. This research method is descriptive qualitative with a case study strategy. Data collection was carried out by observation on history learning activities in the classroom and Kawali’s inscription; informant interviews were conducted by teachers, students and officers of the Astana Gede Kawali Site; and the analysis of documents, syllabus and lesson plans. Purposive sampling and time sampling were used in this study. To find data validity, data triangulation was used. Data analysis used interactive analysis consists of collecting, reducing, presenting data and drawing conclusions. The results of this study indicate the character values in Kawali’s Inscription consist of having the character values of just, hard-working, peace-loving, democratic, respectful, honest, independent, religious, tolerant, caring socially, caring for the environment. The syllabus and lesson plans reflect the implementation of character values based on local wisdom on Kawali’s inscription in learning history. The teacher designs and implements history learning by integrating historical subject matter with the surrounding environment to explore the potential of character values in Kawali’s Inscription to form better, adaptive and positive student characters to meet life’s needs and face challenges in solving everyday problems.Penelitian ini bertujuan untuk mendeskripsikan nilai-nilai karakter Prasasti Kawali dan implementasi nilai karakter berbasis kearifan lokal pada Prasasti Kawali dalam pembelajaran sejarah. Metode penelitian ini adalah deskriptif kualitatif dengan strategi studi kasus. Pengumpulan data dilakukan dengan observasi terhadap kegiatan pembelajaran sejarah di kelas dan prasasti Kawali; wawancara informan dilakukan oleh guru, siswa dan petugas Situs Astana Gede Kawali; dan analisis dokumen, silabus dan RPP. Purposive sampling dan time sampling digunakan dalam penelitian ini. Untuk mengetahui validitas data digunakan triangulasi data. Analisis data yang digunakan analisis interaktif terdiri dari pengumpulan, reduksi, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan nilai-nilai karakter dalam Prasasti Kawali terdiri dari memiliki nilai karakter adil, pekerja keras, cinta damai, demokratis, hormat, jujur, mandiri, religius, toleran, peduli sosial, peduli lingkungan. Silabus dan RPP mencerminkan penerapan nilai-nilai karakter berbasis kearifan lokal pada prasasti Kawali dalam pembelajaran sejarah. Guru merancang dan melaksanakan pembelajaran sejarah dengan mengintegrasikan materi pelajaran sejarah dengan lingkungan sekitar untuk menggali potensi nilai-nilai karakter dalam Prasasti Kawali untuk membentuk karakter siswa yang lebih baik, adaptif dan positif untuk memenuhi kebutuhan hidup dan menghadapi tantangan dalam memecahkan masalah sehari-hari.